Evaluation of solid medical waste management system in Undata Regional General Hospital, Palu city, Central Sulawesi Province, Indonesia - Fadel Banna Palita; Hartuti Purnaweni; Yanuar Luqman (Journal of Bioresources and Environmental Sciences, 2024)
Waste is an environmental problem that is still not fully resolved properly even though the resulting impact has a major effect on environmental pollution, especially solid medical waste. The purpose of this study was to assess the characteristics of solid medical waste at Undata Hospital based on its sources and types, calculate the average weight of solid medical waste generated per day, and evaluate the solid medical waste management system with sorting, packaging, collection and transportation modes in accordance with the criteria of Permen of Environment and Forestry Number 56 of 2015 and Permenkes Number 2 of 2023. This research uses a qualitative approach with a descriptive research type. This research was conducted in August-September 2023. The sampling technique in this study used Purposive Sampling, with 18 informants selected from each unit/room/installation at Undata Hospital, Palu City. Based on the results of the study, it was found that every day Undata Palu Hospital produces domestic waste as much as ± 270 kg / day. The results of the evaluation of the solid medical waste management system at Undata Palu Hospital show that basically it is quite effective but not optimal, because the storage process shows non-compliance with the guidelines for medical waste management by the Ministry of Health Number 2 of 2023, namely storage in TPS which should not be more than 2x24 hours, but in fact the accumulation of solid medical waste is stored for 1 month in the LB3 TPS due to delays in transportation by third parties. This causes a large amount of solid waste in the TPS so that the TPS becomes full and dangerous because the waste undergoes a process of decomposition and decay, which is harmful to the environment and human health. Undata Hospital needs to maximize the procurement of internal medical waste processing equipment (incineration equipment) which needs to be supported by the Environmental Agency and the relevant Health Office to prevent environmental pollution from medical activities.